GP85 The irish experience in paediatric parry romberg syndrome- a case series highlighting management and surgical outcomes. (June 2019) - Egan, Aileen; Flynn, Aoibheann; Watson, Rosemarie; Murray, Dylan
Abstract : Parry Romberg Syndrome (PRS) - also known as Progressive Hemifacial Atrophy- is a rare disorder primarily affecting the soft tissues on one side of the scalp and face, existing on a spectrum with linear scleroderma and 'en coup de sabre' morphoea. Its myriad presenting features, ranging from skin dyspigmentation, thickening or atrophy, hair loss, ophthalmic, dental involvement or even seizures, mean these patients often encounter a variety of specialists before arriving at a diagnosis or commencing on a treatment regimen. Primarily a clinical diagnosis, many children undergo adjunctive blood-based and radiological investigations. Thermographic imaging is also utilised as a non-invasive measure of disease activity, and has been demonstrated to compliment clinical assessment in our cohort. Dermatologists are key in the instigation and monitoring of responses to treatment, which are primarily a regimen of methotrexate and/or pulsed methylprednisolone. Lesions that do not regress with treatment may leave significant facial soft tissue contour defects of the forehead, periocular region, cheek or jaw, which can be socially stigmatising and stressful for these children. Our case series assessed the outcomes for ten children with PRS who underwent facial fat-grafting for these residual sequelae. This included five male and five females, with an age of symptom onset ranging from 3 to 11 years. All completed a single course of immunosuppressant therapy under dermatologic supervision without relapse. After a mean time to stabilisation of 3.5 years, referral to a dedicated Paediatric Plastic and Craniofacial surgeon was made. Thereafter, time to lipofilling ranged from one to twelve months. Patients underwent a mean of 1.3 autologous fat grafting procedures, with very favourable results and no complications. There were no relapses following treatment. To date, this is one of the largest paediatric series reporting outcomes regarding the efficacy of surgery in the management of Parry Romberg Syndrome. It demonstrates a safe, reproducible and well-tolerated procedure for paediatric patients with a condition requiring true multidisciplinary management, and highlights a need for increased awareness across specialties.